Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Pada Toko Cat De’lucent Paint - Satdiah, Alimatuts; Siska, Elmira; Indra, Natal (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to analyze the effect of price, product quality on the decision to buy paint at the Paint De'lucent Paint shop. This research design uses a quantitative approach. Samples were taken by accidental sampling technique which was collected by distributing questionnaires when the buyer was shopping at a paint shop. The analytical method used is validity and reliability test, classical assumption test, multiple linear regression analysis and hypothesis testing by processing using the SPSS program. The results of this study show that price has a negative but not significant effect on, while purchasing decisions have a positive and significant effect on purchasing decisions. Simultaneously, both price and product quality affect the decision to buy paint